Knowledge of Nurses who Work in Maternities about Abortion (Universitas Medica, 2024)
Objective: To understand the knowledge of nurses who work in maternity wards about abortion. Method: Qualitative research approach. An interview was used following a semi-structured script with 15 nurses who work in two maternity hospitals in a medium-sized city in the Brazilian Northeast. The data were processed using the IRaMuTeQ software. Results: 5 classes were obtained, these were categorized thematically, generating 3 categories: types of abortion: spontaneous and induced; abortion identification and procedure; nursing actions for the care of women who have miscarried. Nurses are familiar with spontaneous and induced abortion, influencing their view of the problem, identifying bleeding and pain as signs and recommending humanized care. Conclusion: Spontaneous abortion causes more commotion among professionals, they identify characteristics of the abortion process and develop psychological support actions for these women. Greater discussions are needed on the topic, from training to strengthening permanent education spaces.